Speculative document evaluation - Macdonald, Alexander J.; Brailsford, David F.; Bagley, Steven R.; Lumley, John (2007)
Optimisation of real world Variable Data printing (VDP) documents is a dicult problem because the interdependencies between layout functions may drastically reduce the number of invariant blocks that can be factored out for pre-rasterisation.